Performance Analysis of Costs Implementation Using the EVM Method (Earned Value Method) on the Work of Expanding the Distribution Pipeline Network in Samarinda City - Patanduk, Apriyanto Iring; Oetomo, Wateno; Marleno, Risma (LPPM of NAROTAMA UNIVERSITY, 2024)
In implementing a project, it is often found that implementation does not conform to the plan. Where the problems raised in this research relate to the cost performance of implementing the Samarinda City distribution pipe network expansion project. With the increasing need for clean water and the increasing population, PDAM Kota Samarinda must be able to meet demand with quality, quantity, continuity and accessible prices, as well as adequate water pressure. In an effort to provide clean water services, the government must pay special attention to developing the distribution network. The previous distribution piping network in Samarinda City is considered to need to be expanded to meet the need for clean water, especially during the dry season where there is a shortage of clean water in the Samarinda area. Based on this problem, it is necessary to analyze the condition of the distribution pipe network for clean water services based on the population and calculations for the current year and projections at PDAM Kota Samarinda. Therefore, it is necessary to carry out research related to cost performance analysis on the Samarinda City distribution pipe network expansion work project to determine the position of the project in relation to costs from the monitoring carried out. The research method uses calculations and analysis using the Earned Value Method. Based on the analysis of the data obtained, it can be concluded that the cost performance is not in accordance with the budget and the estimated cost until the project is completed is IDR. 20,583,636,709, greater than the planned IDR. 16,566,678,000.